2019
DOI: 10.1371/journal.pone.0216012
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid modeling of the coupled eye-brain system and insights into simulated microgravity conditions

Abstract: This work aims at investigating the interactions between the flow of fluids in the eyes and the brain and their potential implications in structural and functional changes in the eyes of astronauts, a condition also known as spaceflight associated neuro-ocular syndrome (SANS). To this end, we propose a reduced (0-dimensional) mathematical model of fluid flow in the eyes and brain, which is embedded into a simplified whole-body circulation model. In particular, the model accounts for: (i) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…7 Aside from in vivo measurements, a mathematical model of fluid flow in the eyes and brain embedded into a simplified whole-body circulation model predicted raised ICP and IOP in microgravity. 19 This model predicted decreased ocular blood flow to the choroid and ciliary body whereas retinal circulation was found to be less susceptible to microgravity induced changes.…”
Section: Pathophysiology Of Sansmentioning
confidence: 90%
See 1 more Smart Citation
“…7 Aside from in vivo measurements, a mathematical model of fluid flow in the eyes and brain embedded into a simplified whole-body circulation model predicted raised ICP and IOP in microgravity. 19 This model predicted decreased ocular blood flow to the choroid and ciliary body whereas retinal circulation was found to be less susceptible to microgravity induced changes.…”
Section: Pathophysiology Of Sansmentioning
confidence: 90%
“…Aside from technology that could be used inflight, there are various reports of novel approaches to increase our understanding of SANS. Salerni et al 19 reported a mathematical model of fluid flow in the eyes and brain which predicted increased ICP and IOP in microgravity, as well as decreased ocular blood flow in the choroid and ciliary body. As noted above, the lymphatic system has been proposed to play a role in contributing to SANS, and Rasmussen et al 32 described a technique that could be used to further our understanding of this.…”
Section: Technology For Studying Sansmentioning
confidence: 99%
“…The dynamics of blood, aqueous humor, and CSF in the eye and in the brain are intrinsically intertwined, with alterations in their flow rates and pressures being associated with several pathological conditions, including glaucoma, NDD and SANS, as discussed in section 2. The study of this complex system via mechanism-driven models is still in its infancy, with most investigations being motivated by research in glaucoma (Carichino et al, 2014;Harris et al, 2019;Sala, 2019;Sala et al, 2019b) and SANS (Nelson et al, 2017;Feola et al, 2018;Kaskar et al, 2019;Salerni et al, 2019).…”
Section: Overview Of Mechanism-driven Models Of the Eye And Their Conmentioning
confidence: 99%
“…Another example, normal tension glaucoma, occurs when IOP is again normal but ICP is reduced and the TLPD is increased, and results in optic nerve cupping and classic changes in vision [1][2][3][10][11][12][13] . Not surprisingly, several groups have suggested that IOP and ICP exist in a delicate balance, and that the manipulation of one pressure can counterbalance abnormalities in the other [14][15][16][17][18][19][20] . Unfortunately, the relative inaccessibility of directly measured ICP in humans, which requires either lumbar puncture or intracranial instrumentation, hinders the direct testing of these hypotheses, especially under conditions of microgravity 21 .…”
Section: Introductionmentioning
confidence: 99%
“…npj Microgravity (2020)19 Published in cooperation with the Biodesign Institute at Arizona State University, with the support of NASA1234567890():,;…”
mentioning
confidence: 99%